Implementasi Pendidikan Inklusif dalam Lembaga Pendidikan Islam : Tantangan dan Solusi - Aldi Zainal; Fitria Azura; Amelia Sofia Putri; Herlini Puspika Sari (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to explore the implementation of inclusive education in Islamic educational institutions, as well as to identify the challenges and potential solutions in its practice. Using a qualitative approach through in-depth interviews and direct observation, the findings reveal significant obstacles such as limited teacher understanding, inadequate supporting facilities, and persistent social stigma toward students with special needs. However, continuous professional development for educators, the provision of inclusive-friendly infrastructure, and increased public awareness have proven effective in gradually addressing these challenges. The study emphasizes the importance of collaboration among government, educational institutions, and the wider community in establishing an equitable and quality Islamic education system that is inclusive for all. These findings also contribute to the development of inclusive education policies grounded in Islamic values.